McKee Wright's 'O Rare Young Man: David McKee Wright's Bulletin debates with Jack Lindsay, 1922-25 (Journal of the Association for the Study of Australian Literature, 2013)
An account of the debate between the poet and editor David McKee Wright and Jack Lindsay.